2022
DOI: 10.1101/2022.03.10.22272236
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EMS prehospital response to the COVID-19 pandemic in the US: A brief literature review

Abstract: This study aimed to analyze prehospital Emergency Medical Services (EMS) response to the COVID-19 pandemic in the US through a brief systematic review of available literature in context with international prehospital counterparts. An exploration of the NCBI repository was performed using a search string of relevant keywords which returned n=5128 results; articles that met the inclusion criteria (n=77) were reviewed and analyzed in accordance with PRISMA and PROSPERO recommendations. Methodical quality was asse… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Previous evaluations examined the role of EMS clinicians taking on new roles in various medical situations, such as wellness checks, scenarios with patients with dementia, and COVID-19 vaccination. [18][19][20][21] In addition to exploring expanded roles for individual clinicians, some research has examined the incorporation of different types of practitioners into the emergency response model, such as a study by Corcoran et al in 2018 that found favorable feedback from police officers when social workers were integrated to respond on-scene to domestic violence calls. 22 Faddy et al examined how one department paired paramedics with mental health nurses to respond to mental health crises in the community more appropriately, 23 and Cacciatore et al examined embedding social workers in fire stations to provide community members and firefighters postcrisis support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evaluations examined the role of EMS clinicians taking on new roles in various medical situations, such as wellness checks, scenarios with patients with dementia, and COVID-19 vaccination. [18][19][20][21] In addition to exploring expanded roles for individual clinicians, some research has examined the incorporation of different types of practitioners into the emergency response model, such as a study by Corcoran et al in 2018 that found favorable feedback from police officers when social workers were integrated to respond on-scene to domestic violence calls. 22 Faddy et al examined how one department paired paramedics with mental health nurses to respond to mental health crises in the community more appropriately, 23 and Cacciatore et al examined embedding social workers in fire stations to provide community members and firefighters postcrisis support.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evaluations examined the role of EMS clinicians taking on new roles in various medical situations, such as wellness checks, scenarios with patients with dementia, and COVID-19 vaccination 18-21. In addition to exploring expanded roles for individual clinicians, some research has examined the incorporation of different types of practitioners into the emergency response model, such as a study by Corcoran et al in 2018 that found favorable feedback from police officers when social workers were integrated to respond on-scene to domestic violence calls 22.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EMS teams as well as ED physicians have assumed new and varied healthcare roles during the pandemic, owing to the overall increased healthcare needs. Provision of vaccinations, managing COVID-19 admissions, and caring for post-COVID-19 sequelae belong to the new spectrum of conditions being managed by most specialties, especially internists, pneumologists, and intensive care unit personnel, all specialties commonly involved in the emergency rooms ( 38 , 39 ). It is essential to note that the COVID-19 pandemic has had a significant impact on the mental health of EMTs, resulting in elevated levels of stress and anxiety ( 40 ), which have led to decreased self-efficacy and sleep quality ( 41 ).…”
Section: Discussionmentioning
confidence: 99%